Perceived pressure to breastfeed negatively impacts postpartum mental health outcomes over time - Grattan, Rebecca E.; London, Sophie M.; Bueno, Georgia E. (Frontiers in Public Health, 2024)
Introduction Positive maternal mental health is associated with improved outcomes for infants, and yet the consideration of maternal mental health is often neglected in breastfeeding interventions. Breastfeeding interventions typically focus on breastfeeding promotion, and do not always include supports for the mother. This may result in isolated perceived pressure to breastfeed, the mental health impacts of which are not well understood. Methods This mixed-methods, longitudinal study examined whether perceived pressure to breastfeed was associated with depression, suicide ideation, anxiety, birth trauma and stress concurrently and 4 weeks later for postpartum mothers. It also examined qualitative experiences of feeding. Results Perceived pressure to breastfeed was associated with increased anxiety, stress and birth trauma symptoms four weeks later. Thematic analysis suggested this may be due to difficulties living up to the “breast is best” ideal, believing breastfeeding was part of success as a mother, lack of choices and autonomy in feeding choices for infants and general lack of support. Discussion As such it appears we may be doing more harm than good by focusing our interventions for breastfeeding primarily on increasing pressure to breastfeed, and interventions should consider strategies for promoting positive maternal mental health alongside breastfeeding.